TERMINOLOGY DATABASE IN THE SERVICE OF LEGAL TRANSLATION: BASIC LAW OF HUNGARY - NOVÁK, Barnabás (Comparative Legilinguistics, 2016)
Throughout the process of legislation many terminological questions have been raised that lawyers – as professionals of the given field – are trying to arrange themselves within the framework of law in a comprehensible way. Difficulties that appear during the clarification and interpretation of notions marked by legal terms might and should be handled via the principles and notions of terminology. In case terminology is used in an incorrect or inaccurate way in a legislative process, professional communication and legal certainty gets violated within the given state. As a result of current scientific and technological development, knowledge acquired in particular areas of expertise is continually expanding, the transmission of this cognition is becoming quicker and quicker, there is an ever-growing cooperation between distinct fields of expertise and the usage of ICT tools is getting more and more active. In the light of the above, this study has a double goal. One of them is to present the possible correlations in terminology and legislation (section II.), the other one is to point out that information technologies are also used as tools of terminology in the form of databases, softwares (section III). The proper management of notions marked by legal terms, achieved by the spreading of terminological knowledge and a wider use of terminological tools, may have a positive effect on the process of legislation and would lead to a better linguistic quality of laws and statutes to be prepared in the future.